ANALYSIS OF PATENT TRENDS BETWEEN 2000 AND 2017 IN THE AREAS OF MEDICAL, DENTAL AND TOILET PREPARATIONS INCLUDING OF PHARMACEUTICALS - Chandubhai, Patel Amitkumar (Asian Journal of Pharmaceutical Research and Development, 2018)
Patent information is highly important for decision makers. Their demand for latest technology trend and competitor analysis poses new challenges with respect to the processing and visualization of large amount of patent data. The aim of present study is to map out research and development (R&D) activities landscape through patent analysis of these identified innovations and patent filing trend in the areas of medical, dental and toilet preparations including of pharmaceuticals. The scope of present work includes the patent search and analysis of relevant patents data from all countries across the world using paid patent database PatSeer. To achieve this, analysis and evaluation have been carried out on patenting trends of available data on following parameters Priority Country, Current Legal Status, Patenting Trends, Major Current Owner of Technologies, Assignee Type, International Patent Classification (IPC) Group Data, Technology Topics.